Exploring street art paintings by microspatially offset Raman spectroscopy. (17th July 2018) - Botteon, Alessandra; Colombo, Chiara; Realini, Marco; Bracci, Susanna; Magrini, Donata; Matousek, Pavel; Conti, Claudia
Abstract: Microspatially offset Raman spectroscopy (micro‐SORS) is a recently developed analytical technique combining SORS with microscopy. With this method, highly diffusely scattering microlayers such as painted stratigraphies can be noninvasively probed. In this study, we explore micro‐SORS for identifying the chemical composition of subsurface layers in real, street art mural paintings as a new nondestructive method for the characterization of their stratigraphy. Two micro‐SORS variants, defocusing and full micro‐SORS, were tested and compared. Abstract : Microspatially offset Raman spectroscopy (micro‐SORS) is an innovative nondestructive method for the characterization of turbid microlayered stratigraphies. In this paper, the method was used to identify the chemical composition of subsurface layers in real, street art mural paintings. Both the variants of micro‐SORS were shown to provide relevant information, also in challenging situation of heterogeneous real samples.